2019
DOI: 10.3390/pharmaceutics11110574
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Combination Nano Therapies for Pancreatic Cancer

Abstract: Pancreatic cancer is one of the deadliest causes of cancer-related death in the United States, with a 5-year overall survival rate of 6 to 8%. These statistics suggest that immediate medical attention is needed. Gemcitabine (GEM) is the gold standard first-line single chemotherapy agent for pancreatic cancer but, after a few months, cells develop chemoresistance. Multiple clinical and experimental investigations have demonstrated that a combination or co-administration of other drugs as chemotherapies with GEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 94 publications
0
35
0
Order By: Relevance
“…Consequently, TA release at T ≈ T m as well as at T > T m would be desirable. Currently, it is unknown whether TA release occurs in the L α phase of DPPC bilayers, as has been reported for other molecules [ 67 , 68 ]. TA release from DPPC:DSPE-PEG (96:4) and DPPC:MPPC:DSPE-PEG (86:10:4) LUVETs was therefore investigated at T > T m during 5 min of heating, i.e., in line with the thrombus dynamics [ 15 ] and previously established complete release times [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, TA release at T ≈ T m as well as at T > T m would be desirable. Currently, it is unknown whether TA release occurs in the L α phase of DPPC bilayers, as has been reported for other molecules [ 67 , 68 ]. TA release from DPPC:DSPE-PEG (96:4) and DPPC:MPPC:DSPE-PEG (86:10:4) LUVETs was therefore investigated at T > T m during 5 min of heating, i.e., in line with the thrombus dynamics [ 15 ] and previously established complete release times [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that the imidazolidone group of biotin forms hydrogen bonds with the imidazole ring of histidine when adsorbed to proteins during accumulation inside tumor cells [50]. Similarly, hydrogen bonding between the biotin ring and imidazolidone group of gemcitabine ( Figure 3B) probably increases the drug-loading capacity [51]. Electrostatic interactions between the drug and the unmodified carboxylate group of PG4.5 may also increase the gemcitabine-loading content of the nanoparticles.…”
Section: Characterization Of Gemcitabine-loaded Nanoparticlesmentioning
confidence: 87%
“…Mice (7 mice/group) were implanted with S2VP10 and S2CP9 cells as stated above. Seven days, (S2VP10) or ten days (S2CP) post-implantation, mice were treated with PBS, 50 mg/kg Gemzar [64,65], 10 µg/kg of echinomycin [62], or 10µg/kg SDC1-Lip echinomycin injected iv weekly for 3 weeks. Mouse survival was assessed as a measure of tumor response because ATP levels measured using bioluminescence imaging are not appropriate with autophagy [17,66].…”
Section: In Vivo Treatment With Sdc1-lip Echinomycinmentioning
confidence: 99%